The old wive's tale - Bennett, Arnold (Oxford University Press, 1995)
This study of the changes wrought by time on the lives of two English sisters during the 19th century is a masterpiece of literary realism. Constance and Sophia Baines, the daughters of a shopkeeper, grow up in the rural town of Bursley. Sophia eventually runs off and settles in Paris with her husband, who is a cad, and Constance remains behind in England and marries the mild-mannered shop assistant. The sisters are reunited years later when they are old, and Bennett skillfully contrasts what has remained stable in their characters with the differences time and environment have produced in their personalities.